On determination of elastic modulus and indentation hardness by instrumented spherical indentation: influence of surface roughness and correction method - Guangjian Peng; Yu Liu; Fenglei Xu; Hanyang Jiang; Weifeng Jiang; Taihua Zhang (Materials Research Express, 2023)
Although, surface roughness can influence the determination of elastic moduli and indentation hardness to some extent by instrumented spherical indentation test, limited work has been done to quantitatively reveal and minimize these influences. In the present work, through a large number of finite element (FE) simulations and analyses, we clarified the evolution trend of determined elastic moduli and indentation hardness corresponding to different normalized indentation depths ( h / R ) and normalized roughness ( S _q / R ). On this basis, an area correction method was proposed to improve the measurement accuracy in the elastic moduli and indentation hardness. The FE results show that, with the newly proposed correction method, the maximum relative error in determined elastic moduli is reduced from about ±7% to ±2%, and that in the determined indentation hardness is reduced from about ±13% to ±5%, when S _q / R ≤ 2.2 × 10 ^−3 and h / R = 5%. Applications were then illustrated on four typical metallic materials (i.e., AA 7075, AA 2014, steel 316 L, and copper T2). The experimental results demonstrate that the proposed correction method is able to mitigate the effects of surface roughness on the determination of elastic moduli and indentation hardness to obtain more correct results.